2017
DOI: 10.1136/bjophthalmol-2017-310812
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy bleb needling and antimetabolite administration practices in the UK: a glaucoma specialist national survey

Abstract: There is a significantly wide variety of current practices for antimetabolite administration and bleb needling within the UK and Ireland. This may be influenced by a glaucoma surgeon's specific experience and audit results as well as particular clinical set-up, availability of antimetabolite and clinic room space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…17 Mercieca K et al performed a cross-sectional online survey distributed to glaucoma specialists in United Kingdom, they reported bleb needling was performed in the operating room by 56 % of responders. 25 In our study, although we performed this procedure at the slit lamp in all cases, there were no major visual threatening complications found. Needling revision is a safe and simple method which can rescue failing blebs.…”
Section: Discussionmentioning
confidence: 55%
“…17 Mercieca K et al performed a cross-sectional online survey distributed to glaucoma specialists in United Kingdom, they reported bleb needling was performed in the operating room by 56 % of responders. 25 In our study, although we performed this procedure at the slit lamp in all cases, there were no major visual threatening complications found. Needling revision is a safe and simple method which can rescue failing blebs.…”
Section: Discussionmentioning
confidence: 55%
“…Different studies have used MMC at doses ranging from 0.004 mg (Mardelli et al, 1996) to 0.04 mg (Shetty et al, 2005). 5‐FU is mostly used at doses of 5 mg but doses up to 25 mg have been reported (Mercieca et al, 2018). Preoperative risk assessment has been recommended to serve as a guide to the approximate dose necessary to achieve surgical success but can be adjusted according to the clinical response (Lama & Fechtner, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that 20%–25% of patients with failed filtering blebs after trabeculectomy required needling with MMC and 5‐FU, respectively (Gutierrez‐Ortiz et al, 2006; King et al, 2007). In a survey completed by 60 glaucoma specialists, 72% preferred 5‐FU and 22% preferred MMC in needling with 12% using either of the two drugs interchangeably (Mercieca et al, 2018). The decision includes the previous needling experience of the glaucoma surgeon, presence of risk factors for failure, the level of intraocular pressure, an assessment of bleb morphology and behaviour of the bleb following trabeculectomy (Labbé & Baudouin, 2014; Mercieca et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tai et al 26 evaluated the shortterm outcomes of NR in a cohort of 58 patients randomized to MMC alone or in association with bevacizumab and found no difference regarding success rates and IOP control, despite a better bleb morphology in the association group. 9,10,17,22 In this study, we retrospectively reviewed the long-term efficacy and safety of office-based NR augmented with 5-FU or betamethasone for impending bleb failure in a large cohort of patients who had previously undergone trabeculectomy or phacotrabeculectomy. In our cohort of patients, NR had a favorable profile in terms of efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%